OPTIMIZING VOLUNTEER PREPARATION TO SUPPORT STUDENT MOBILITY PROGRAM AT UNIVERSITY OF DHYANA PURA - Ni Luh Christine P. Suyasa; Melissa Koch; Putu Chris Susanto (LPPM Universitas Dhyana Pura, 2020)
ABSTRACTThis research aims to optimizing the candidates’ preparation of Diakonie Baden withinformation about Germany prior to departure in relation to culture shock reduction and havingbetter on German language skills. In order to determine the required information, students ofUniversitas Dhyana Pura who went to Germany and currently conducting volunteer program, theInternational office were interviewed. Based on the research data, it resulted the detail informationand practical way on how to live in Germany as well as differences between Germany and Indonesiawhich purposively reduce the culture shock and having better communication. In addition, a Germanclub was established. Interested students can meet the exchange students from Germany and getmore information about Germany and the culture before applying for the volunteer program withDiakonie Baden. This research provides a good starting point in preparing volunteers from Undhirafor Germany, since there are more topics about Germany to cover.Keywords: Culture shock, preparation, student mobility